Book Review: The Malayan Emergency: Essays on a Small, Distant War - Souchou, Yao (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The book is an attempt by an anthropologist of Malaysian origin presently teaching in Sydney to make sense of the Malayan Emergency (1948–1960) by looking at the event from a Marxist perspective. For most Malaysians who are used to the ofcial narrative, this approach oﬀers another way of looking at the same episode in their history by providing an explanation of the failed communist (socialist) revolution in Malaya. Coming from Kuala Lumpur, a petty bourgeois background, the author was aﬀected by the Emergency in many ways just like many of his generation. But unlike others he was attracted to Marxism while studying at Adelaide University in the 1960s. At the time and the subsequent decades, the Marxist theory became fashionable among academics all over the world including Malaysia as it provides an exciting underpinning of the social sciences. Later the author was drawn to the New Left ideology of the Frankfurt School and French Marxists like Althusser.